The Digital Outrage and Distrust: Cancel Culture Against Indonesia’s State-Owned Enterprise - Yudha, Reza Praditya; Hakim, A. Rahman; Phanphongsa, Vanhna (Universitas Muhammadiyah Yogyakarta, 2025)
Cancel culture is commonly associated with public figures. However, in the era of digital hyperconnectivity, this practice has increasingly targeted state institutions. This study examines how Indonesian netizens construct and mobilize cancel culture in response to a high-profile corruption scandal involving executives of the state-owned oil and gas company, Pertamina. This research is critical for understanding the intersection between crisis communication, public agenda-setting, and digital social control within the context of state-owned enterprises. The study employs a virtual ethnography approach, with data collected through a social listening tool, Brand24, from Instagram and X (formerly Twitter) between February 1st and March 11th, 2025. Findings reveal that the public orchestrated collective pressure using popular words and digital symbols, including emojis and politically charged hashtags. The crisis was widely interpreted as indicative of systemic failure and elite interference. In this case, cancel culture emerged as a form of civic articulation against the lack of transparency, delayed institutional communication, and the erosion of public trust in the state.